Disposición a la aceptación de la educación a distancia como modalidad de estudios, a partir de las experiencias de formación en época de pandemia. - Valdiviezo Parra, Ximena Carolina (2024)
ABSTRACT: This study aims to investigate the impact of virtual training experience during the pandemic on the preference for online education among Economics students at UNACH. The research employs a quantitative, non-experimental approach utilizing a questionnaire for data collection. The questionnaire comprises two sections: the first gathering socioeconomic data, and the second assessing the quality of virtual education processes. The survey's validation draws from preliminary studies by Segovia and Hugs, with a sample of 257 surveys collected. Given the study's nature, logit and probit models were utilized for analysis, with the confusion matrix employed to assess model significance, determining that the Logit model performs best. Results indicate that in section II, four components significantly impact the model: the effect of the pandemic on emotions and educational difficulties, the overall evaluation of virtual education experience during the pandemic, home internet connection type, and administrative process effectiveness. In section III, it is evident that four out of the five measured qualities exhibit significant components.